Remote School Students’ Perspectives on Endemic and Endangered Animals: Knowledge, Reasons, and Solutions Approach - Reni Marlina; Erwina Oktavianty; Haratua Tiur Maria Silitonga; Hamdani Hamdani; Afandi Afandi (Jurnal Pendidikan Indonesia, 2022)
Environmental degradation, which is mostly caused by human behavior, has resulted in the increasing number of endangered endemic animals. It is very important to identify the implications of education in junior high school through the KRS approach. This study aims to analyses reveal student perspectives through open questionnaires with reasons, and interviews related to knowledge, reasons, and solutions in protecting EA which can be implemented in Conservation-based Education (CBE) at remote school. The population was comprised of remote school students at a public school consisting of 434 students. The sample involved was 25% of the total population who filled out the EA questionnaire, then 25% of the total students who filled out the questionnaire, namely 26 students were sampled in semi-structured interviews. Data analyses is carried out using tabulation table in the form of an Excel sheet, and processing was carried out using SPSS to obtain information about the total score, mean, CPR, and category of each statement item. The result of this study found that the role of the KRS approach on EA is an effort to establish. Conservation-based Education (CBE) in remote schools is based on the perspective of students which is designed in lesson plans by prioritizing the outcomes in the form of increasing knowledge of the sustainability of EA's existence, description of strategies and stages of EA protection, and  the formation of an EA lover group in collaboration with tourism office so that it has a clear direction of development regarding the existence of EA.